Women's contribution to rangeland cultivation: a policy blind spot - Najjar, Dina (International Center for Agricultural Research in the Dry Areas, 2024)
The blog highlights the gender-specific challenges faced by Tunisian women in managing rangelands, emphasizing the need for inclusive policies. Despite active involvement in livestock activities, women encounter hurdles due to limited land ownership, impacting access to resources. Dr. Dina Najjar's study stresses the importance of recognizing women's contributions and tailoring policies to their needs, addressing climate change responses, training, and research disparities. Investing in women's equal access to land is crucial for sustainable land management.